• 6x-9 ; x = -2 • 2x²+5 ; x = -2
6(-2)-9 = -21 2(-2)²+5 = 13
• 6x-9 ; x = -1 • 2x²+5 ; x = -1
6(-1)-9 = -15 2(-1)²+5 = 7
• 6x-9 ; x = 0 • 2x²+5 ; x = 0
6(0)-9 = -9 2(0)²+5 = 5
• 6x-9 ; x = 1 • 2x²+5 ; x = 1
6(1)-9 = -3 2(1)²+5 = 7
• 6x-9 ; x = 2 • 2x²+5 ; x = 2
6(2)-9 = 3 2(2)²+5 = 13
• x²-3x+2 ; x = -2 • 3x³+2x²-x+8 ; x = -2
(-2)²-3(-2)+2 = 12 3(-2)³+2(-2)²-(-2)+8 = -6
• x²-3x+2 ; x = -1 • 3x³+2x²-x+8 ; x = -1
(-1)²-3(-1)+2 = 6 3(-1)³+2(-1)²-(-1)+8 = 8
• x²-3x+2 ; x = 0 • 3x³+2x²-x+8 ; x = 0
(0)²-3(0)+2 = 2 3(0)³+2(0)²-(0)+8 = 8
• x²-3x+2 ; x = 1 • 3x³+2x²-x+8 ; x = 1
(1)²-3(1)+2 = 0 3(1)³+2(1)²-(1)+8 = 12
• x²-3x+2 ; x = 2 • 3x³+2x²-x+8 ; x = 2
(2)²-3(2)+2 = 0 3(2)³+2(2)²-(2)+8 = 38
Step-by-step explanation:
hope it help;)